REVISITING THE EBOLA EPIDEMIC IN WEST AFRICA: THE ROLE OF EMOTIONAL DETERMINANTS IN PUBLIC RESPONSES - KOUSOULIS, Antonis; GRANT, Imogen; DUNCAN, Joshua; LARSON, Heidi (African Journal of Infectious Diseases (AJID), 2023)
Background: The 2014-2016 Ebola epidemic was largely restricted to the three nations of Guinea, Liberia and Sierra Leone, yet it tested the world’s ability to address a potential global pandemic. This study provides an in-depth examination of the role of emotions in the response to the outbreak and engagement with public health measures, and the contextual factors which influenced them. Methods: Historical research methods were utilised in the examination of primary and secondary sources. A multi-faceted SPEECH (Society and Politics, Economy, Epidemiology, Culture, Healthcare and Public Health) framework was developed to aid data synthesis and analysis. Results: The outbreak occurred in a region still reeling from years of civil war, where poverty was widespread and healthcare severely underfunded. Internationally, global health security had been politically neglected. After a slow start, the international response to the outbreak was strong, yet the lack of community engagement and inadequate consideration of local culture and traditional beliefs, fueled fear and hindered engagement with professionals and uptake of public health measures. Improved collaboration and communication with rural communities in the latter phases of the response was crucial in effectively addressing the outbreak. Conclusion: This study illustrates the importance of effective collaboration between international crisis responders, in-country public health practitioners and local communities in addressing public emotional responses to the Ebola outbreak. It highlights how community engagement and communications tactics can effectively be utilised to soothe and educate the public, abating counterproductive extreme emotional responses, and in turn improving uptake of public health measures.